An experimental study on the hover performance characteristics of the coaxial propellers configuration for the drone - Kim, D.K.; Yoon, B.I.; Song, Y.H.; Song, J. (My University, 2018)
Drone (or Passenger Drone) is one of hot issues in eVTOL industry present. So many companies such as Ehang, Airbus, Volocopter, Uber, Workhorse, etc. release their new concept taxi drone. In near future (within 2030), this taxi drone will enter commercial market and taxi service company (ex: Uber) will start to enter service only if these drones are commercialized. One of this taxi drone is required at the urban air mobility environment. This request compact sized vehicle operated between urban buildings with heavy payload which need to cover passengers. So, several candidate concept of taxi drone such as E-hang 184, Workhorse Surefly introduce the coaxial propellers design. Also, the more heavier payload with given sized vehicle drive these coaxial propellers drone described in figure1 [1] The purpose of this study is to present reliable performance data by experimental studying coaxial propellers configuration and to identify the characteristics of coaxial propellers to be used at the design, production, and verification and performance evaluation. To do this, experimental device was developed that can test at low Reynolds number(Re?3105) of coaxial propellers. The experimental device basically constructed the DAQ which can measure torque, rpm, power so that the performance characteristics of the upper and lower propellers can be known. The experiments which composed of the different H/D ratio (0.1~0.8) defined as the ratio of distance of upper / lower propellers divided by its diameter and the different propellers diameters ratio were conducted. Experiments were carried out on the coaxial propeller after verifying the calibration. As a result of comparing the values with F.M.(Figure of Merit), it was found that the coaxial propeller of the same diameter showed a constant FM at the H/D ratio(0.2~0.3) and the highest value of all conditions tested was achieved when the diameter of the upper part of the propeller was smaller than the diameter of the lower part confirmed.